2002
DOI: 10.1074/jbc.m110476200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of High Affinity Binding to Group III Metabotropic Glutamate Receptors

Abstract: The amino-terminal domain containing the ligand binding site of the G protein-coupled metabotropic glutamate receptors (mGluRs) consists of two lobes that close upon agonist binding. In this study, we explored the ligand binding pocket of the Group III mGluR4 receptor subtype using site-directed mutagenesis and radioligand binding. The selection of 16 mutations was guided by a molecular model of mGluR4, which was based on the crystal structure of the mGluR1 receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…The microenvironment within the mGluR4 binding pocket encompasses several positively charged amino acids that recognize the negatively charged phosphonate group of group III selective compounds such as L-AP4 and L-SOP. Our finding that the mGluR4 residues, K74, E287, and K317, contribute collectively to subgroupselective ligand binding are in agreement with previous mutagenesis studies on mGluR4 (14) and analogous mutations in other mGluR subtypes (15)(16)(17). The Ser-313 residue has not previously been identified as important for ligand binding and subtype selectivity, and even though it was not as effective as the others, it still showed a clear increase in affinity, especially in the case of quisqualic acid.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The microenvironment within the mGluR4 binding pocket encompasses several positively charged amino acids that recognize the negatively charged phosphonate group of group III selective compounds such as L-AP4 and L-SOP. Our finding that the mGluR4 residues, K74, E287, and K317, contribute collectively to subgroupselective ligand binding are in agreement with previous mutagenesis studies on mGluR4 (14) and analogous mutations in other mGluR subtypes (15)(16)(17). The Ser-313 residue has not previously been identified as important for ligand binding and subtype selectivity, and even though it was not as effective as the others, it still showed a clear increase in affinity, especially in the case of quisqualic acid.…”
Section: Discussionsupporting
confidence: 79%
“…The rationale by which mutations were chosen was based on sequence alignment of the mGluR ATDs (Table I) (14) and by comparing the homology model of mGluR4 with the crystal structure of mGluR1. The non-conserved residues, Lys-74 in lobe I and Glu-287, Ser-313, and Lys-317 in lobe II (see Table I), were chosen for this study on the grounds that they lie within the glutamate binding pocket and are oriented toward the distal carboxylate of glutamate, which is presumably supplanted by the heterocyclic rings of quisqualic acid and ibotenic acid (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies revealed two major conformational changes resulting from agonist binding. A first one is the closure of at least one VFTM in the dimer, as expected from modeling studies of other family 3 GPCRs (6,(8)(9)(10)20). Indeed, glutamate binds to lobe I within the cleft that separates both lobes and also can interact with residues from lobe II leading to the stabilization of a closed state.…”
mentioning
confidence: 73%
“…As other GPCRs, family 3 receptors have a heptahelical domain (HD) responsible for G protein activation (2). However, they possess a large, extracellular domain structurally similar to bacterial periplasmic-binding proteins that contain the agonist-binding site (3)(4)(5)(6)(7)(8)(9)(10). As clearly shown by the solved x-ray structure of the glutamate-binding domain of the metabotropic glutamate receptor type 1 (mGlu1 receptor) (11), this domain is constituted of two lobes separated by a large cleft on which agonists bind and is called a Venus flytrap module (VFTM).…”
mentioning
confidence: 99%